Understanding Generation X’s Adoption of Digital Payment Systems: An Integrated Utaut–ToE Perspective - Yunus, Muhammad Haekal; Nurjannah, Nurjannah; Zainuddin, Ahmad Fuad; Erwina, Erwina (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines Generation X’s intention to adopt digital payment systems by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) with the Technology–Organization–Environment (ToE) framework. It contributes to the fintech adoption literature by explicitly disentangling individual-level behavioral drivers from organizational and environmental constraints, thereby clarifying why adoption among Generation X remains uneven despite widespread technological diffusion. Using survey data from 200 Generation X respondents and analyzing the model with PLS-SEM, we find that UTAUT constructs, including performance expectancy, effort expectancy, social influence, facilitating conditions, and trust, significantly predict adoption intention. In contrast, ToE-related factors exhibit weaker explanatory power, suggesting limited salience of organizational and environmental conditions for this cohort. These findings imply that policies and managerial strategies aimed at accelerating fintech adoption among Generation X should prioritize behavioral alignment and digital confidence rather than structural or institutional interventions.